2001
DOI: 10.1002/jlcr.25804401229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chayotte (Sechium edule) extract on the biodistribution of technetium‐99m and on the morphometry of red blood cells

Abstract: 28 de setembro, 87, Rio de Janeiro, RJ, Brasil, 2055 1-030. bemardo@uerj.br key words: Sechiunz edule, blood cells, technetium-99m, biodistribution, morphometry. summary.The evidence that drugs can affect radiolabeling or biodistribution of red cells in setting of nuclear medicine clinic has with to light only recently. A therapeutic drug can modify the nature/amount of technetium-99m ehTc) radiopharmaceutical bound to blood elements and this may result in a unexpected behavior of the radiopharmaceutical. Chay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…Passos et al (2000; have also demonstrated that dietary conditions can interfere with the biodistribution of radiobiocomplex. Several authors have also reported that, due to their pharmacological properties, some chemical compounds can alter the biodistribution of various radiobiocomplexes (Brito et al, 1998;Diré et al, 2003;Gomes et al, 2002;Diré et al, 2001;Grigoleit and Grigoleit, 2005;Hesslewood and Leung, 1994;Aguiar et al, 2002;Gomes et al, 2001;Mattos et al, 1999;Mattos et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passos et al (2000; have also demonstrated that dietary conditions can interfere with the biodistribution of radiobiocomplex. Several authors have also reported that, due to their pharmacological properties, some chemical compounds can alter the biodistribution of various radiobiocomplexes (Brito et al, 1998;Diré et al, 2003;Gomes et al, 2002;Diré et al, 2001;Grigoleit and Grigoleit, 2005;Hesslewood and Leung, 1994;Aguiar et al, 2002;Gomes et al, 2001;Mattos et al, 1999;Mattos et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that medicinal plants contain mixtures of various pharmacologically active compounds, and thus may have the potentiality to interfere with the labeling of radiobiocomplexes (Capriles et al, 2000;Amorim et al, 2003;Diré et al, 2004;Lima et al, 2003;Moreno et al, 2002;Moreno et al, 2005;Oliviera et al, 2002;Oliviera et al, 2003;Santos-Filho et al 2004) and/or with their biodistribution Capriles et al, 2000;Diré et al, 2003;Moreno et al, 2005;Diré et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A distribuição, a fixação e a eliminação de radiofármacos em um organismo dependem de vários fatores, tais como o fluxo sanguíneo, o metabolismo tecidual e a ligação aos elementos sanguíneos 4,15 . Vários autores têm demonstrado que a biodisponibilidade de radiofármacos pode ser modificado por produtos naturais e sintéticos [6][7][8][9][10][11][12][13]22 .…”
Section: Discussionunclassified
“…. Essas hemácias marcadas também têm sido de importância em vários estudos clínicos e também experimentais de possível interesse para a pesquisa na medicina nuclear [4][5][6][7][8][9][10][11] . Essa marcação é baseada na capacidade de redução do cloreto estanoso (SnCl 2 ) que atua sobre o 99mTc, na forma de pertecnetato de sódio.…”
Section: Resumo -Objetivounclassified
See 1 more Smart Citation